Video consultation as nursing practice during early in‐home care for premature infants and families viewed from the families' homes' - Mai‐Britt Hägi‐Pedersen; Hanne Kronborg; Annelise Norlyk (Wiley, 2021)
Abstract Aim This study examined how communication between nurses and families in video consultations in a neonatal early in‐home care program unfolded in the context of parents' homes. Design A qualitative study based on focused observations supported by audio‐recorded video consultations. Methods The data were collected through nine video consultations between nurses and families in an early in‐home care program. The transcribed material was examined using inductive content analysis. Findings The analyses revealed the following themes: "Setting the scene," "Weight as a point of reference" and "The pros and cons of technology." The video consultations unfolded in a relaxed atmosphere, but also as one‐way communication dominated by nurses, with the infant's weight as the focus. The study finds that a focus on training in video communication is needed to take full advantage of video consultations' potential.